PENERAPAN ARSITEKTUR NEO-VENAKULAR PADA PERANCANGAN MINANGKABAU CULTURAL ART CENTER DI KABUPATEN TANAH DATAR - Viona Mita Shaly; Putri Suryandari; Harfa Iskandaria (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
ABSTRACT The Minangkabau Art and Culture Center educates culturalists and the general public about Minangkabau culture, as well as introducing Minangkabau culture to domestic visitors through Minangkabau art performances and cultural displays.Therefore, with the design of an Art Center Area, it is hoped that it can accommodate community activities in the fields of religious education, economics and sports and can respond to the need for open space in the city of Solo. The Art Center area applies the concept of Contemporary Architecture as an effective form of approach to the surrounding community, especially for teenagers. As a result of the Minangkabau Arts and Culture Center's architecture, it is believed that it would be able to accommodate community activities in the areas of art, culture, and tourism. And it is capable of meeting the need for open space in Tanah Datar Regency. The Minangkabau Art and Culture Center employs the Neo-Vernacular Architecture idea as a means of reaching out to the surrounding community, particularly the Minangkabau people. Keywords: Tanah Datar Regency, Minangkabau Culture, Arts Center